Evaluation of Skirt-Raft Foundation Performance Adjacent to Unsupported Excavations - Ahmed, Balqees A.; Saleh, Husam M.; Jameel, Mina M.; Al-Taie, Asmaa (Civil Engineering Journal, 2024)
The continuous demand for urban development, along with the construction of new buildings, highways, and infrastructure, creates an increasing necessity for excavation activities. Deep excavation near existing buildings can lead to ground instability, potentially causing structural damage to nearby properties. This research aims to investigate methods for enhancing buildings stability from the initial stages of construction, focusing on protecting structures from potential future adjacent excavations. This study utilizes a skirt-raft foundation system, modeled using the finite element software PLAXIS 3D, to evaluate its effectiveness in improving stability and protection. The study analyzed the behavior of raft foundations in clay soil adjacent to excavations ranging from 1 m to 10 m and compared this with the performance of raft foundations with added skirt foundations. The comparison focused on settlement, rotation, and lateral movement of the excavations to assess potential building damage. The results showed that incorporating a skirt foundation significantly enhanced structural stability and reduced excavation-related damage. The implementation of a skirt foundation to a depth of 0.5B (where B is the foundation width) for excavations of similar depth has been shown to significantly reduce damage levels from medium or high to light while also decreasing differential settlement by 80%. It is recommended that adjacent excavation depths should not exceed 0.25B. However, if a skirt foundation is constructed at a depth of 0.5B, the excavation depth can be safely extended to 0.75B. Doi: 10.28991/CEJ-2024-010-12-018 Full Text: PDF